2007
DOI: 10.1080/14992020701311168
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability of distortion-product otoacoustic emissions in children with normal hearing: A preliminary study

Abstract: The test-retest reliability of DPOAEs was investigated in 24 children (43 ears) with normal hearing at five F2 frequencies (2530, 3561, 5014, 7029, and 10,028 Hz). Two DPOAE recordings were performed on the same subjects in the same location using the same equipment. The second recordings were made 13 to 15 days after the first recording. The DPOAE level recorded in the subjects ranged between -13.10 and 20.20 dB for all the five frequencies. The variation in DPOAE level was greater at 10,028 Hz than at other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
9
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 14 publications
7
9
1
Order By: Relevance
“…Reavis et al [32] proposed that a DPOAE reduction of 4 dB or greater at adjacent f 2 frequencies constituted an ototoxic change. However, both of these studies were conducted in adults, and the criterion selected for this study was more consistent with the limits exceeding normal variation in children identified by Sockalingam et al [28]. In addition, the finding that three children receiving high cumulative dosages of carboplatin were identified as having ototoxic change in DPOAE levels was in agreement with previous research in animal models.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Reavis et al [32] proposed that a DPOAE reduction of 4 dB or greater at adjacent f 2 frequencies constituted an ototoxic change. However, both of these studies were conducted in adults, and the criterion selected for this study was more consistent with the limits exceeding normal variation in children identified by Sockalingam et al [28]. In addition, the finding that three children receiving high cumulative dosages of carboplatin were identified as having ototoxic change in DPOAE levels was in agreement with previous research in animal models.…”
Section: Discussionsupporting
confidence: 87%
“…Currently, there is no universal agreement on the criterion for ototoxic change using OAE tests. Sockalingam et al [28] calculated minimal changes in DPOAE level that exceeded the limits of test-retest reliability at individual f 2 frequencies in children aged 5–12 years. Based on their data, the average minimal change exceeding the limits of normal variation at four f 2 frequencies between 2530–7029 Hz was 6.47 dB.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, high test-retest reliability is reported for TEOAEs (Harris et al, 1991;Vedantam & Musiek, 1991;Franklin et al, 1992;Engdahl et al, 1994;Marshall & Heller, 1996;Dieler et al, 1999) as well as for DPOAEs (Franklin et al, 1992;Roede et al, 1993;Zhao & Stephens, 1999;Shehata-Dieler et al, 1999;Beattie & Bleech, 2000;Beattie et al, 2003;Hallenbeck & Dancer, 2003;Ng & McPherson, 2005;Mills et al, 2007;Sockalingam et al, 2007;Wagner et al, 2008). Test-retest measurements without probe-replacement has the smallest amount of variability which is indicative for the intrinsic variability of emission amplitudes, while a larger variability is determined after probe-refi tting.…”
Section: Sumariomentioning
confidence: 93%
“…There are several factors contributing to the variability of EOAE amplitude. First, the reliability is affected by the recording instrument, calibration, test parameters, and environmental factors (Zhao & Stephens, 1999;Hallenbeck & Dancer, 2003;Mills et al, 2007;Sockalingam et al, 2007), as well as subject-generated noise during breathing, swallowing, muscle and joint movement, or vascular pulsation (Vedantam & Musiek, 1991;Zhao & Stephens, 1999;Hallenbeck & Dancer, 2003;Sockalingam et al, 2007). External, environmental noise can be caused by the probe-tip placement, i.e.…”
Section: Sumariomentioning
confidence: 99%
“…Test/retest reliability of DPOAEs has been examined thoroughly in humans to assess the clinical usefulness of this measure (for recent studies, see Sockalingam et al ., 2007; Wagner et al ., 2008; Stuart et al ., 2009; Keppler et al ., 2010). However, reliability of DPOAEs has been examined less thoroughly in animals, and in only a few animal models (Harding et al ., 2002; Rasmussen et al ., 2005; Parrazini et al ., 2006; Park et al ., 1995).…”
Section: Introductionmentioning
confidence: 99%